1976
DOI: 10.1136/jcp.29.7.652
|View full text |Cite
|
Sign up to set email alerts
|

Pneumonia caused by coliforms and Pseudomonas aeruginosa.

Abstract: NW3soNopsis The diagnosis and treatment of 20 hospital patients seen in the past year with proven pneumonia caused by coliforms and Pseudomonas aeruginosa are discussed. Predisposing factors and methods for improving laboratory and clinical diagnosis are analysed, the main problem being to discriminate between genuine pneumonia caused by these organisms and mere contamination of sputum samples resulting from colonization of the upper respiratory tract following broad-spectrum chemotherapy.Overall initial chemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1977
1977
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 15 publications
(13 reference statements)
0
8
0
Order By: Relevance
“…Furthermore, the model used [22] was very close to human pseudomonal pneumonia, especially with regard to bacterial concentration [23][24][25][26][27][28][29][30][31], and was also close to the human therapeutic situation since human-like pharmacokinetics was successfully achieved. In these conditions, we found that continuous infusion of CAZ with or without TOB was the most effective regimen.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the model used [22] was very close to human pseudomonal pneumonia, especially with regard to bacterial concentration [23][24][25][26][27][28][29][30][31], and was also close to the human therapeutic situation since human-like pharmacokinetics was successfully achieved. In these conditions, we found that continuous infusion of CAZ with or without TOB was the most effective regimen.…”
Section: Discussionmentioning
confidence: 99%
“…Early and accurate escalation of gentamicin doses may be clinically important in children with serious Gram-negativeinfections, particularly Gram-negative pneumonia for which serum concentrations greater than 8J.lg/ ml are optimal (Darrell et al, 1967;Noone et al, 1976Noone et al, , 1978. The new model provides a simple and more accurate method for individualising paediatric and adolescent doses within the first few hours of therapy.…”
Section: Therapeutic Implicationsmentioning
confidence: 98%
“…Peak serum concentrations higher than 4 to 5J.lg/ml (Darrell and Waterworth, 1967; Jackson and Riff, 1971;Nooneetal., 1974Nooneetal., , 1978are Age (years) considered optimal for treatment of serious Gramnegative infections, with concentrations greater than 8]Jg/ml (Noone and Rogers, 1976;Noone et aI., 1978) desirable for Gram-negative pneumonia. On the other hand, concentrations greater than 12J.lg/ml are not recommended because of the increased risk of ototoxicity (Hewitt, 1973;Jackson and A'reieri, 1971;Wersall et al, 1969) while nadir (pre-dose) concentrations exceeding 2 J.lg / ml appear to increase the risk of nephrotoxicity (Dahlgren et aI., 1975;Goodman et al, 1974).…”
mentioning
confidence: 99%
“…When aerobic, gram-negative rods that cause urinary tract infection, skin and soft-tissue infection, or bacteremia were treated with gentamicin, a post-dose concentration of 15 mg/L given in the first 3 days of therapy was related to a good response. In patients with pneumonia caused by gram-negative rods, post-dose concentrations of 18 mg/L were related to beneficial outcome [5][6][7].…”
mentioning
confidence: 99%